2021
DOI: 10.1002/1873-3468.14167
|View full text |Cite
|
Sign up to set email alerts
|

Selective increment of phosphatidylserine on the autophagic body membrane in the yeast vacuole

Abstract: In yeast cells, the autophagosome is a double‐membrane structure; the inner membrane becomes the autophagic body membrane in the vacuole. Vacuolar enzymes degrade the autophagic body. There is no critical information regarding its selective degradation. Using the electron microscopy method, distributions of four phospholipids were examined in the autophagosomal and autophagic body membranes upon autophagy induction. The labeling of phosphatidylserine (PtdSer) in the autophagic body membrane dramatically increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Atg15 activity against PS is significantly higher than those against PE, for example [ 16 ]. Thus, within the vacuolar lumen, Atg15 could preferentially hydrolyze PS present at the membrane outsides of ABs but absent from the inside of the vacuole membrane [ 17 ]. However, upon overexpression, the small activity of Atg15 against other lipids might be sufficient to be detrimental for cellular growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atg15 activity against PS is significantly higher than those against PE, for example [ 16 ]. Thus, within the vacuolar lumen, Atg15 could preferentially hydrolyze PS present at the membrane outsides of ABs but absent from the inside of the vacuole membrane [ 17 ]. However, upon overexpression, the small activity of Atg15 against other lipids might be sufficient to be detrimental for cellular growth.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, a later study found that Atg15 acted as a phospholipase with a substrate preference for phosphatidylserine (PS) but with lesser activity; also, cardiolipin and phosphatidylethanolamine were hydrolyzed [ 16 ]. During the course of this project, freeze–fracture electron microscopy showed the accumulation of PS on the outer membrane leaflet of autophagic bodies, while it was rare on the inside of the vacuole [ 17 ]. This would explain how Atg15 can mediate the lysis of autophagic bodies without affecting the integrity of the vacuole.…”
Section: Introductionmentioning
confidence: 99%